Visual perception and attentional skills in school-age children: A cross-sectional study of reading proficiency in the hearing impaired - Renu Thakur; Jaikishan Jayakumar; Sangeeta Pant (Wolters Kluwer Medknow Publications, 2023)
Background: Auditory impairment is one of the common sensory deficits that occur in humans. Hearing loss affects students' ability to communicate and read, which eventually causes social and scholastic stigma. Reading relies heavily on phonics as well as visual attention. Students with normal hearing read by transforming phonic sounds into words. Hearing impaired has little to no phonic ability, making them visual readers who rely on visual cues while reading. Present study sought to investigate factors that affect reading skills in hearing-impaired children. Material and Methods: A cross-sectional study was conducted in hearing- and hearing-impaired schools of Ludhiana, Punjab, India. After vision screening among all students, sixty students were enrolled via convenient sampling. Higher order of visual perception, attention, and reading ability was investigated. Results: A total of 60 students were evaluated (30 hearing impaired and 30 age-matched hearing). The hearing group was statistically better than the hearing impaired (p = 0.001), Hearing impaired were better in visual attention (p = 0.001), whereas a correlation was found between reading ability and visual perception, attention skill of hearing- and hearing-impaired students (r = 0.80, P = 0.001). Conclusion: Present study concludes that hearing-impaired students exhibit issues with visual-motor integration, visual-spatial relationships, and visual sequential memory. Higher visual attention was demonstrated by hearing-impaired students. The results of the current investigation revealed a correlation between visual perception and attention skills and reading competency. Thus, the present study demands that the newly enrolled hearing-impaired students must undergo a thorough ocular evaluation.